Internationalization strategies of the Greek MNEs during the pre-crisis period: An econometric research based on the OLI model - Dimitris Giakoulas; Constantina Kottaridi (SPOUDAI - Journal of Economics and Business, 2020)
This study is an effort to explore the impact of various determinants on Greek Outward Foreign Direct Investment from 2001 till the outbreak of the debt crisis in Greece. The case of Greece is of great interest of how a small peripheral EU country in the southern neighborhood drove its internationalization path before the outbreak of the financial crisis. Specifically, investigating the way in which Greece's participation in the single market and the oncoming crisis affected the internationalization of Greek MNEs is of utmost importance. A main contribution of this paper is that it examines ownership and location advantages at specific sectors of an economy. We do so by analyzing disaggregated firm level data and examining separately the sectors of trade and manufacturing. We are building our theoretical framework on Dunning's eclectic paradigm which perceives firms' internationalization as a result of the combination of Ownership advantages, Location advantages and Internationalization advantages. This model allows as to link the internal micro-environment of the firm with the external macro environment of the host country and also to investigate specific motives of internationalization for each sector. Our results indicate that there is a major and incontrovertible impact of the tax rate of the host country to the Greek MNEs. Moving forward at sector level analysis for the manufacturing and the trade sectors, we found that Dunning and Lundan's (2008) conceptualization on the motives of internationalization is validated.
Keywords: F23; 330; FDI; Multinational Enterprises; determinants; internationalization; Greece; debt crisis